2013
DOI: 10.1016/j.ppnp.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear chiral dynamics and thermodynamics

Abstract: This presentation reviews an approach to nuclear many-body systems based on the spontaneously broken chiral symmetry of low-energy QCD. In the low-energy limit, for energies and momenta small compared to a characteristic symmetry breaking scale of order 1 GeV, QCD is realized as an effective field theory of Goldstone bosons (pions) coupled to heavy fermionic sources (nucleons). Nuclear forces at long and intermediate distance scales result from a systematic hierarchy of one-and two-pion exchange processes in c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
145
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(149 citation statements)
references
References 189 publications
(305 reference statements)
4
145
0
Order By: Relevance
“…It simultaneously provides the foundation for systematic nuclear structure studies of few-and many-body systems. Current state-of-the-art potentials 12 have progressed to chiral order N 4 LO (fifth order in Q/Λ) and achieved still further substantial improvements in comparison with empirical NN two-body data, including peripheral phase shifts and np polarization observables [58,59]. Convergence has been successfully demonstrated by investigating dominant contributions of order N 5 LO [60].…”
Section: Nuclear Many-body Forcesmentioning
confidence: 99%
See 2 more Smart Citations
“…It simultaneously provides the foundation for systematic nuclear structure studies of few-and many-body systems. Current state-of-the-art potentials 12 have progressed to chiral order N 4 LO (fifth order in Q/Λ) and achieved still further substantial improvements in comparison with empirical NN two-body data, including peripheral phase shifts and np polarization observables [58,59]. Convergence has been successfully demonstrated by investigating dominant contributions of order N 5 LO [60].…”
Section: Nuclear Many-body Forcesmentioning
confidence: 99%
“…Various applications of in-medium chiral perturbation theory have been reported in recent years (see [12,13] and refs. therein).…”
Section: Nuclear Many-body Forcesmentioning
confidence: 99%
See 1 more Smart Citation
“…For symmetric matter it was found that low-momentum NN plus 3N interactions are capable to predict realistic saturation properties, with 3N forces fit only to few-body data [7], whereas neutron matter was found to be perturbative [8]. In subsequent studies, symmetric matter and neutron matter were also investigated based on chiral EFT interactions within the self-consistent Green's function framework [9,10], using coupled-cluster theory [11,12], with in-medium chiral perturbation theory [13] and in many-body perturbation theory [14]. Furthermore, the development of novel local chiral NN forces opened the way to first Quantum Monte Carlo studies of neutron matter based on chiral EFT interactions [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…One finds pc 0.3 GeV which is comparable to that of cold nuclear matter at twice saturation density. Of course, one should keep in mind that the chiral condensate at T pc is still at about half of its vacuum value, which, again is in the vicinity of recent estimates in cold nuclear matter at twice nuclear saturation density [13]. Figure 1: Dilepton spectra in heavy-ion collisions from HADES at SIS [3] (left), CERES [5] and NA60 [6] at SPS (middle panels) and STAR [7] at RHIC (right panel), compared to theoretical calculations with QGP and hadronic emission using the same model for the in-medium ρ spectral function [9,10,11,12].…”
Section: Introductionmentioning
confidence: 67%